2006
DOI: 10.1038/sj.icb.7100004
|View full text |Cite
|
Sign up to set email alerts
|

Positive reactions on Western blots do not necessarily indicate the epitopes on antigens are continuous

Abstract: Epitope mapping (identification of an antigenic site recognized by an antibody) is an important component of vaccine development and immunological assays. It is widely accepted that in Western blots, antibodies react exclusively with continuous epitopes: discontinuous epitopes are assumed to be irreversibly destroyed by electrophoresis under the denaturing conditions used for sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Here, we demonstrate that the epitopes recognized by four different monoclona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 41 publications
(70 reference statements)
1
24
0
Order By: Relevance
“…All data together suggested that the epitope of mAb 1A11 was not linear. It has been previously reported that conformational epitopes can be detected by Western blot, probably because of epitope renaturation during or after the transfer of the protein to the blotting membrane (51). Thus, we speculate that mAb 1A11 may bind to a conformational epitope of BACE1.…”
Section: Mab 1a11 Binds To Unique Structures On Bace1: Loops D and F-mentioning
confidence: 89%
“…All data together suggested that the epitope of mAb 1A11 was not linear. It has been previously reported that conformational epitopes can be detected by Western blot, probably because of epitope renaturation during or after the transfer of the protein to the blotting membrane (51). Thus, we speculate that mAb 1A11 may bind to a conformational epitope of BACE1.…”
Section: Mab 1a11 Binds To Unique Structures On Bace1: Loops D and F-mentioning
confidence: 89%
“…However, our findings indicate that, subsequent to denaturing treatments, PrP readily refolds during or after Western blotting to a structure amenable to detection by conformation-dependent antibodies. Although it is widely assumed that discontinuous epitopes are generally irreversibly destroyed under the denaturing conditions used for SDS-PAGE, positive reactions on Western blots with antibodies recognizing discontinuous epitopes are not without precedent (44).…”
Section: Discussionmentioning
confidence: 99%
“…However, a caveat needs to be raised regarding the long held perception that antibodies bind in western blots to only linear epitopes, in the light of recent findings by Zhou et al that challenge this view, with evidence that Ab-binding to discontinuous regions can occur. They have suggested that this is possible as a result of protein refolding of secondary structures during gel-blot processing [21]. …”
Section: Human Antibodies Bind To Denatured Surface Envelope and Intementioning
confidence: 99%